Developing and securing the cloud - Thuraisingham, Bhavani M. (CRC Press, 2014)
"Supplying a comprehensive overview of cloud computing technology, this book provides step-by-step instruction on how to develop and secure the cloud. It provides an easy-to-understand, basic level overview of cloud computing and supporting technologies. It describes a framework for cloud computing and web services. It discusses the layers of the framework, cloud security, private and public clouds, and clouds developed by the US government and academia"--